2018
DOI: 10.5455/apd.285285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prevalence of metabolic syndrome in patients with schizophrenia and bipolar disorder: a cross-sectional study from Black Sea region

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…We found that BMI was associated with the presence of MetS in both NCEP and IDF. This report was in line with the study conducted in Palestine, 28 Turkey, 29 and Brazil. 25 Moreover, the study conducted in Palestine, 28 also indicated that the duration of SMI was significantly associated with the presence of MetS.…”
Section: Factors Associated With Mets Among Patients With Severe Mentsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that BMI was associated with the presence of MetS in both NCEP and IDF. This report was in line with the study conducted in Palestine, 28 Turkey, 29 and Brazil. 25 Moreover, the study conducted in Palestine, 28 also indicated that the duration of SMI was significantly associated with the presence of MetS.…”
Section: Factors Associated With Mets Among Patients With Severe Mentsupporting
confidence: 92%
“…18 which was 28.9%. However, the higher rate of MetS was reported by different international studies: 43.6% in Palestine, 28 32.3% in Turkey, 29 34.7% in Kashmir, 30 49% in Australia, 31 and 32% in South Africa 32 in NCEP criteria. In addition, higher rates also were reported by different studies using IDF like 35% in Hong Kong, 9 54% in Australia, 31 32.8% in Italy, 33 and 38.1% in Egypt.…”
Section: Factors Associated With Mets Among Patients With Severe Mentmentioning
confidence: 78%
See 1 more Smart Citation
“…23 In this study, the prevalence of low HDL-c (<40 mg/dl) was 69.4%. It was inconsistent with the rate reported from different studies like 42.1% in India, 24 48.4% in Seoul, South Korea, 23 52% in Palestine, 25 58.5% in Southwest Ethiopia, 19 56% in Korea, 26 52.5% in Durban, South Africa, 27 42.5% among major depressive disorder patients and 25% among schizophrenic patients in Egypt, 28 47.7% among schizophrenic and bipolar patients in Turkey, 29 52.5% in Saudi Arabia, 30 35.2% among schizophrenic patients in Singapore, 31 and 23% in Hong Kong. 32 However, the depicted studies used cutoff limit <40 mg/dl in males and <50 mg/dl in female to define low HDL-c; whereas <40 mg/dl was used as a cutoff limit for both sex as described in 2002 NCEP-ATP III guidelines and this might be a reason for the rate variation between the studies.…”
Section: Discussionmentioning
confidence: 59%
“…Conversely, the finding was higher than the prevalence reported from several studies like 17.5% in India 24 and 14.5% in Durban, South Africa. 27 Higher prevalence rate also were reported from different international studies like 46% in Korea, 26 32.8% in Saudi Arabia, 30 44.1% in South Korea schizophrenic patients, 23 49.2% in Palestine, 25 42.5% in major depressive patients and 30% in schizophrenic patients in Egypt, 28 53.6% among schizophrenic and bipolar disorder patients in Turkey, 29 and 29% in South Africa. 33 However, the degree of disturbances of lipid profile induced by different generations of antipsychotic agents, duration of antipsychotic therapy, nutritional habit, and location could show a disparity in the prevalence rate between the studies.…”
Section: Discussionmentioning
confidence: 61%